Desarrollo de un hemisintético de celulosa y su implementación como matriz de intercambio iónico (2024)
In the present study, the functionalization of cellulose, obtained from orange peels, was carried out using chemical methods in order to use it for the deionization of controlled electrolytic media. For this, two functionalization routes were explored: the first sought the sulfonation of the polymer using fuming sulfuric acid, and the second the oxidation of the primary alcohols of cellulose, using potassium permanganate, to obtain carboxylate groups. The obtained samples were studied by FTIR spectroscopy and differential scanning calorimetry (DSC) to corroborate the physical and chemical changes before and after the functionalization process. The products obtained from the functionalization were used in the deionization of aqueous media with CaCl2 and MgCl2 dissolved in concentrations of 0.01, 0.025 and 0.050 M. The cation exchange capacity of the resin was calculated, obtaining a value of 1.6 meq / ml, and the measurement results indicated a decrease of up to 50% in the concentration of the evaluated cations in the solutions.